2019
DOI: 10.1002/ana.25416
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting cessation of status epilepticus in clinical practice: Data from a prospective observational registry (SENSE)

Abstract: Objective: To investigate the initial termination rate of status epilepticus (SE) in a large observational study and explore associated variables. Methods: Data of adults treated for SE were collected prospectively in centers in Germany, Austria, and Switzerland, during 4.5 years. Incident episodes of 1,049 patients were analyzed using uni-and multivariate statistics to determine factors predicting cessation of SE within 1 hour (for generalized convulsive SE [GCSE]) and 12 hours (for non-GCSE) of initiating tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
4
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 36 publications
0
98
4
10
Order By: Relevance
“…130 A recent study on status epilepticus in eight German and Austrian emergency units revealed that LEV is used as a first-line agent sporadically with inferior efficacy compared with benzodiazepines. 131…”
Section: Clinical Studies In Status Epilepticusmentioning
confidence: 99%
“…130 A recent study on status epilepticus in eight German and Austrian emergency units revealed that LEV is used as a first-line agent sporadically with inferior efficacy compared with benzodiazepines. 131…”
Section: Clinical Studies In Status Epilepticusmentioning
confidence: 99%
“…[1][2][3][4][5] Refractory SE (RSE) and superrefractory SE (SRSE) are characterized by the failure of first-, second-, and third-line therapy and, in the latter case, anesthetic therapy. It requires instant medical intervention and is accompanied by prolonged hospital stays and increased health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…It requires instant medical intervention and is accompanied by prolonged hospital stays and increased health care costs. [1][2][3][4][5] Refractory SE (RSE) and superrefractory SE (SRSE) are characterized by the failure of first-, second-, and third-line therapy and, in the latter case, anesthetic therapy. 1,6 There are few controlled or randomized study data on RSE and SRSE, so that the basis of therapeutic management frequently relies on expert opinion, clinical reports, and pathophysiological assumptions arising from experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, randomized controlled trials showed no benefit of starting with an iv AED (PB, PHT) instead of a benzodiazepine (32), or to administer an iv AED (LEV) coupled with benzodiazepine as first-line treatment (Navarro et al 2016;Treiman et al 1998). A large European retrospective study including over a thousand of patients found no superiority of one particular benzodiazepines but demonstrated that use of benzodiazepines as first treatment step and higher cumulative dose of anticonvulsant independently predict SE cessation (Kellinghaus et al 2019), highlighting the importance to use benzodiazepines, at adequate dosage, at the beginning of an SE episode.…”
Section: Clonazepam (Clz)mentioning
confidence: 99%